2010
DOI: 10.1029/2009wr008758
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling of nutrient losses in streams: Interactions of climatic, hydrologic, and biogeochemical controls

Abstract: [1] We present an analytical, stochastic approach for quantifying intra-annual fluctuations of in-stream nutrient losses induced by naturally variable hydrologic conditions. The relevance of the problem we address lies in the growing concern for the major environmental impacts of increasing nutrient loads from watersheds to freshwater bodies and coastal waters. Here we express the first-order nutrient loss rate constant, k e , as a function of key biogeochemical and hydrologic controls, in particular the strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 72 publications
(119 reference statements)
0
46
0
Order By: Relevance
“…The studies of Runkel (2007), Botter et al (2010), and Argerich et al (2011) also showed that λ HZ can be estimated from the hydrologic transport and solute reaction kinetics. Thus, we calculated λ HZ as:…”
Section: Hyporheic Hydrologic Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…The studies of Runkel (2007), Botter et al (2010), and Argerich et al (2011) also showed that λ HZ can be estimated from the hydrologic transport and solute reaction kinetics. Thus, we calculated λ HZ as:…”
Section: Hyporheic Hydrologic Conditionsmentioning
confidence: 95%
“…The effective NO 3 -removal rate at the reach scale, λ tot (/h), can be represented as the sum of the NO 3 -removal rate in the surface stream channel and benthic layer, λ stream (/h), and in the HZ, λ HZ (/h) as suggested by Runkel (2007) and Botter et al (2010):…”
Section: Hyporheic Hydrologic Conditionsmentioning
confidence: 99%
“…This modeling framework has been widely used in stream systems where the groundwater-surface water exchange constitutes an important component of nitrogen cycling [Botter et al, 2010;Basu et al, 2011;Stewart et al, 2011] and can be used to link the physical geometry to nutrient retention in a parsimonious manner. This model can be written as: The PFR model has been used extensively in stream literature at watershed and continentals scales due to its simplicity and its spatiotemporal averaging of the fine-scale processes.…”
Section: Methods Of Modelling Nutrient Retention In Streamsmentioning
confidence: 99%
“…Research on the role of river networks in global nutrient cycles has identified factors such as stream temperature, the supply of biogenic nutrients, respiration rates and contact time of water with sediments as the key variables affecting nutrient retention [Boyer et al, 2006;Alexander et al, 2009]. Both mass balance and stream tracer studies have revealed an inverse relationship between nutrient retention potential and stream depth, thus leading to a higher nutrient retention potential of small streams compared to larger rivers [Seitzinger et al, 2002;Peterson et al, 2001;Alexander et al, 2000;Botter et al, 2010;Basu et al, 2011;Ye et al, 2012].…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation